2003
DOI: 10.1210/en.2003-0097
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Voluntary Exercise on the Mouse Hypothalamic-Pituitary-Adrenocortical Axis

Abstract: We studied the effects of long-term (i.e. 4 wk) voluntary exercise on the hypothalamic-pituitary-adrenocortical (HPA) axis in male mice. Voluntary exercise was provided by giving mice access to a running wheel, in which they indeed ran for about 4 km/d. Exercising mice showed similar body weights as control animals but presented less abdominal fat, lighter thymuses, and heavier adrenal glands. Exercise resulted in asymmetric structural changes in the adrenal glands. Whereas control mice had larger left than ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
275
7
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(321 citation statements)
references
References 97 publications
38
275
7
1
Order By: Relevance
“…The moderate and short-lasting effects of mifepristone on voluntary running activity suggest that motivating effects may possibly be initiated via a GR-dependent mechanism, but not their persistence. This is in agreement with the observation that GR levels were found to be unaltered by 4 weeks of voluntary wheel running, despite a downregulation of the high affinity mineralocorticoid receptors [13] which may thus contribute more to motivation to exercise than GRs.…”
Section: Corticosterone Synthesis Motivates Voluntary Wheel Runningsupporting
confidence: 92%
See 1 more Smart Citation
“…The moderate and short-lasting effects of mifepristone on voluntary running activity suggest that motivating effects may possibly be initiated via a GR-dependent mechanism, but not their persistence. This is in agreement with the observation that GR levels were found to be unaltered by 4 weeks of voluntary wheel running, despite a downregulation of the high affinity mineralocorticoid receptors [13] which may thus contribute more to motivation to exercise than GRs.…”
Section: Corticosterone Synthesis Motivates Voluntary Wheel Runningsupporting
confidence: 92%
“…Forced exercise has a stressful component that may contribute to its effects on the brain [11]. Although less stressful than forced exercise [11], voluntary wheel running also activates the hypothalamic pituitary adrenocortical (HPA) axis and elevates plasma levels of the stress hormone corticosterone [12,13]. Interestingly, corticosterone, when induced or administered at sufficient levels, has direct reinforcing and rewarding properties and enhances reinforcing and rewarding effects of abused drugs via activation of the low affinity glucocorticoid receptor (GR) [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…However, short, intense stressor(s) can also compromise animal well-being and induce distress as a response to acute stress (Moberg, 2000). In fact, despite the fact that most acute stress responses (like the 'flight or fight response') seem to be beneficial and desirable for the animal (as they promote a physical and physiological adaptation to the environment), some naturally rewarding behaviours, such as exercise, can also induce an acute stress response in a very similar profile to that which produces distress (Droste et al, 2003). As regards horses, different studies have reported either negative or positive physical and physiological effects due to an acute stress response during exercise (Langsetmo et al, 2000;Moberg, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, an explanation might be found in one of the properties of wheel running. Voluntary wheel running causes an increase in plasma corticosterone levels in female house mice [11] and male C57 mice [9]. We performed a pilot study aimed at investigating the relation between wheel running and corticosterone in DBA and C57 mice and found that already after 90 min of wheel exposure there was an increase in plasma corticosterone.…”
Section: Inbred Strain Differences In Wheel Runningmentioning
confidence: 98%